A new locus for non-syndromal, autosomal recessive, sensorineural hearing loss (DFNB16) maps to human chromosome 15q21-q22. Issue 12 (December 1997) - Campbell, D A; McHale, D P; Brown, K A; Moynihan, L M; Houseman, M; Karbani, G; Parry, G; Janjua, A H; Newton, V; al-Gazali, L; Markham, A F; Lench, N J; et al.
Abstract : Non-syndromal, recessive deafness (NSRD) is the most common form of inherited deafness or hearing impairment in humans. NSRD is genetically heterogeneous and it has been estimated that as many as 35 different loci may be involved. We report the mapping of a novel locus for autosomal recessive, non-syndromal deafness (DFNB16) in three consanguineous families originating from Pakistan and the Middle East. Using multipoint analysis (HOMOZ/MAPMAKER) a maximum combined lod score of 6.5 was obtained for the interval D15S1039-D15S123. Recombination events and haplotype analysis define a 12-14 cM critical region between the markers D15S1039 and D15S155 on chromosome 15q15-q21.